Impact of Pparβ/δ deletion in non-parenchymal cells - liver physiology and disease (NAFLD) - Chen, Kelvin Jiapeng (2018)
Non-alcoholic fatty liver disease (NAFLD) is causing an alarming health issue in developed countries. NAFLD can progress from steatosis to non-alcoholic steatohepatitis (NASH) characterized by liver inflammation, leading to cirrhosis and hepatocellular carcinoma (HCC). Mice with impaired macrophage activation, when fed a high-fat diet, develop severe NASH. Evidence is mounting that Kupffer cells are implicated. However, it is unknown whether the resident CD68+ or bone marrow-derived CD11b+ Kupffer cells are involved. The characterisation of the liver of a new FSP1cre-Pparβ/δ-/- mouse model revealed FSP1 is expressed in CD11b+ Kupffer cells. Although these cells only constitute a minute fraction of the liver cell population, Pparβ/δ deletion in these cells led to remarkable hepatic phenotypic changes. We report higher lipid content was present in P2 FSP1cre-Pparβ/δ-/- livers, which diminished after weaning. Genes that are involved in fatty acid β-oxidation and lipid biogenesis were upregulated in P2 FSP1cre-Pparβ/δ-/- livers. Several mechanisms have been reported to result in developing liver steatosis. They often lead to decrease in β-oxidation and promote lipid biogenesis, which in turn increase the level of lipids in the hepatocytes. Our study revealed the involvement of bone morphogenetic protein 8B precursor (BMP8b) in regulating lipid homeostasis in hepatocytes. We observed that there is a negative correlation between BMP8b and lipid biogenesis. Our in vitro study demonstrated that supplementing liver cells with BMP8b resulted in alteration of PPARα and PPARβ/δ gene expression. In parallel, genes that are involved in fatty acid β-oxidation and lipid biogenesis were downregulated. Hence, we propose that FSP1cre-Pparβ/δ-/- mice, which accumulate lipids in their liver in early life due to lower BMP8b level, may be a good animal model to study juvenile NAFLD.